The Effect of Biologically Active Additives on the Duration of the Larval Period and Vitality Indicators of the Mulberry Silkworm - Obidjonovna, Zikirova Mashxura; Aliyevich, Jumagulov Qaxramon (American Journal of Botany and Bioengineering, 2024)
In this article, 0.5%, 1.0%, and 3.0% solutions of Stevioside, prepared from the Stevia plant, were added to the mulberry silkworm feed as biologically active additives, and the duration of the larval period of silkworms maintained in ordinary drinking water and traditional worm feeding methods. and their viability indicators are compared, and the results of the study on the effect of biologically active additives on the silkworm are given.